Hubungan Kualitas Tidur dengan Kesehatan Mental pada Perawat di RS Sari Asih Cipondoh - Umi Lailatussa’adah; Wigyo Susanto; Betie Febriana (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The nursing profession is a shift-based profession. Night shifts can impact sleep quality, which in turn disrupts sleep quality. Seven factors influence sleep quality, most commonly experienced by nurses. Poor sleep negatively impacts mental health. This study aims to explore the relationship between sleep quality and mental health among nurses at Sari Asih Cipondoh Hospital. This study was quantitative with a cross-sectional approach. Sampling was conducted using probability sampling and simple random sampling, with a total of 111 respondents. Univariate and bivariate analyses were performed using the Chi-Square Test, with a significance level of p<0.05. Respondent characteristics indicate that the majority were women aged 25 to 35, working in inpatient units with less than five years of work experience. Most nurses at Sari Asih Cipondoh Hospital reported poor sleep quality. The mental health of nurses at Sari Asih Cipondoh Hospital was within the normal range. There is a relationship between sleep quality and mental health of nurses at Sari Asih Cipondoh Hospital using the Chi Square Test, a P value of 0.000 (<0.05) was obtained. There is a relationship between sleep quality and mental health of nurses at Sari Asih Cipondoh Hospital using the Chi Square Test, a P value of 0.000 (<0.05). Therefore, this study can provide suggestions for nurses to be able to implement sleep pattern strategies so that sleep quality is in the good category.